Factors associated with delivery outside a health facility: cross‐sectional study in rural Malawi. Issue 5 (2nd March 2015) - Mazalale, Jacob; Kambala, Christabel; Brenner, Stephan; Chinkhumba, Jobiba; Lohmann, Julia; Mathanga, Don P.; Robberstad, Bjarne; Muula, Adamson S.; De Allegri, Manuela
Abstract Objective To identify factors associated with delivery outside a health facility in rural Malawi. Method A cross‐sectional survey was conducted in Balaka, Dedza, Mchinji and Ntcheu districts in Malawi in 2013 among women who had completed a pregnancy 12 months prior to the day of the survey. Multilevel logistic regression was used to assess factors associated with delivery outside a facility. Results Of the 1812 study respondents, 9% (n = 159) reported to have delivered outside a facility. Unmarried women were significantly more likely [OR = 1.88; 95% CI (1.086–3.173)] to deliver outside a facility, while women from households with higher socio‐economic status [third‐quartile OR = 0.51; 95% CI (0.28–0.95) and fourth‐quartile OR = 0.48; 95% CI (0.29–0.79)] and in urban areas [OR = 0.39; 95%‐CI (0.23–0.67)] were significantly less likely to deliver outside a facility. Women without formal education [OR 1.43; 95% CI (0.96–2.14)] and multigravidae [OR = 1.14; 95% CI (0.98–1.73)] were more likely to deliver outside a health facility at 10% level of significance. Conclusion About 9% of women deliver outside a facility. Policies to encourage facility delivery should not only focus on health systems but also be multisectoral to address women's vulnerability and inequality. Facility‐based delivery can contribute to curbing the high maternal illness burden if authorities provide incentives to those not delivering at the facility without losing existing users.